2005
DOI: 10.1590/s1415-47572005000300020
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Xanthomonas axonopodis pv. citri based on plasmid profile and pulsed field gel electrophoresis

Abstract: Xanthomonas axonopodis pv. citri strains that cause disease in citrus were investigated by pulsed field and plasmid profile analysis. For the first method, genomic DNA was digested by the rare-cutting enzymes Xba I and Vsp I. The strains evaluated were collected in seven different States of Brazil and in Argentina, Bolivia, Paraguay and Uruguay. Genetic variability was found among strains of X. axonopodis pv. citri from different geographical areas Argentina, Bolivia and Uruguay, with similarities varying from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The variable plasmid configuration, that we observed in Xc-A strains in this study, was also previously reported by Amuthan & Mahadeban [ 32 ], and Carvalho et al [ 9 ]. Recently, it was determined in specific strains of Pseudomonas syringae pv.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The variable plasmid configuration, that we observed in Xc-A strains in this study, was also previously reported by Amuthan & Mahadeban [ 32 ], and Carvalho et al [ 9 ]. Recently, it was determined in specific strains of Pseudomonas syringae pv.…”
Section: Discussionsupporting
confidence: 90%
“…However, plasmid variation was not considered in their study. In 2005, Carvalho et al [ 9 ] characterized the genetic diversity of 22 X. citri A-type strains from South America. Based on the comparison of plasmid profiles, and based on RFLPs identified via pulsed-field-gel electrophoresis, the authors observed high coefficients of similarity for strains isolated in similar geographical locations (from 0.83 to 1 for strains isolated in seven Brazilian states and between 0.62 and 0.83 for strains from Argentina, Bolivia, Paraguay and Uruguay).…”
Section: Introductionmentioning
confidence: 99%
“…Important reasons for the lack of knowledge are due to the great genetic variability of phytopathogens as the X. fastidiosa and Xanthomonas spp., the slow-growth of the fungus P. citricarpa and ineffective tentatives in culturing the bacterium Candidatus Liberibacter spp. Therefore, these challenges require deeper biochemical and chemical studies (Carvalho et al, 2005;Nunney et al, 2014;Frare et al, 2019;Merfa et al, 2019).…”
Section: Final Remarks and Future Perspectivesmentioning
confidence: 99%
“…A relatively high amount of genetic diversity was observed among isolates, indicating that there might be distinct pathotypes of the bacterium present in Malaysia. Carvalho et al (2005) investigated X. axonopodis pv. citri strains by pulsed-field and plasmid profile analysis.…”
Section: Morphological Characteristics Of Isolated X Axonopodis Pv Citrimentioning
confidence: 99%